(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Nurses have effect on patient education on a heart disease. The educational role of nurses helps to improve their health. The study’s goals are to determine the roles of nurses in health education. Materials and Methods:This study was conducted at selected hospitals in Erbil, from June 20, 2021, to January 20, 2022. A sample of 123 nurses was interviewed, with the questionnaire consisting of three parts: socio-demographic, educational roles for patients, and learning practices for patient adaptation. The study aimed to identify the health education and practical roles among nurses. The reliability of the questions was 0.926, indicating acceptable reliability. Results: The majority of participants were aged between 32 and 42. Female nurses comprised 55.3%, with 57.3% holding diploma. Nurses’ educational role in patient care, with 65% performing well. 59.3% taught patients’ healthy habits, and 65% effectively educated patients about self-care. The study reveals a significant relationship between nurses’ socio-demographic factors, their overall educational role, and nurses’ overall learning role. The good educational role was significantly associated with the hospitals they worked in and their units (P <0.001). Nurses also demonstrated good learning roles in their qualifications. However, the learning role was not significant with the other socio-demographic. Conclusion: Most nurses play an important role as an educator while patients are in the hospital and after they leave. There was a strong relationship between their roles, their qualifications, and the units in which they worked.